Scholarly Publishing Practices among LIS Lecturers in Higher Institutions of Learning in Nigeria - Okechukwu, Obediah Chukwuka; Ndubuisi-Okoh, Elizabeth E.; Okoche , Chukwu; Oladokun, Bolaji David (Journal of Digital Learning and Education, 2024)
This study investigates the scholarly publishing practices among LIS lecturers in Nigerian higher education institutions, focusing on their publishing outlets, perceived barriers, and necessary skills for successful publishing. Utilizing a descriptive survey design, the study gathered data from 362 LIS educators across Nigerian institutions through a questionnaire, analyzed using descriptive statistics. The study reveals that LIS lecturers in Nigerian higher education institutions have positive perceptions of scholarly publishing, recognizing its importance for professional growth and career advancement. Furthermore, the findings indicate that while academic journals are the primary outlet for communicating research findings, LIS lecturers also utilize a range of other channels, including conference proceedings, books, social media, and collaborative research projects, highlighting a diverse approach to scholarly dissemination. The findings emphasize the paramount importance of skills required to navigate the scholarly publishing process effectively. The study recommended that higher institutions of education should implement mentorship and training programs specifically designed to support lecturers in developing the skills needed for scholarly publishing.